Radiographic evaluation of apical root resorption of maxillary first molars after intrusion using zygomatic skeletal anchorage - Al-Masry, Mazin (My University, 2004)
Araştırmanın amacı açık kapanış olgularında zigomatik ankraj kullanılarak yapılan üst arka bölgenin gömülmesi sonucunda, üst birinci azılarda oluşabilecek apikal kök rezorpsiyonunun radyografik olarak değerlendirilmesidir. Çalışma grubu kliniğimizde açık kapanışları zigomatik kemiğe yerleştirilen özel titanyum miniplaklar aracılığıyla üstçenenin arka bölgesine gömme kuvveti uygulanarak kapatılan 16 olgudan oluşmuştur. Kontrol grubu aynı yaş, cinsiyet ve tedavi sürelerine sahip, ancak intruzyon mekaniği içermeyen sabit ortodontik tedavi görmüş olgular arasından seçilmiştir. Tedavi öncesi ve tedavi sonrası panoramik radyografiler üzerinde üst birinci azıların mesiobukkal ve distobukkal köklerinin uzunlukları bir bilgisayar yazılımı yardımıyla ölçülmüştür. İki grubun apikal kök rezorpsiyonlarının istatistiksel olarak karşılaştırılması sonucunda sağ mesiobukkal kök için istatistiksel olarak anlamlı bir fark bulunmuştur. Ancak aradaki ortalama farkın sadece 0.5 mm olması nedeniyle bu farkın klinik olarak anlamlı olmadığı sonucuna varılmıştır. RADIOGRAPHIC EVALUATION OF APICAL ROOT RESORPTION OF MAXILLARY FIRST MOLARS AFTER INTRUSION USING ZYGOMATIC SKELETAL ANCHORAGE English

The aim of our study was to evaluate radiographically the apical root resorption of maxillary first molars after their intrusion done using zygomatic implant as a skeletal anchorage in open bite cases and to evaluate whether the intrusion of posterior teeth can be one of the risk factors associated with apical root resorption. The study group comprised sixteen consecutively treated openbite cases, who had received special titanium miniplates in their zygomatic bones as anchorage to apply orthodontic intrusive forces to the maxillary posterior region. The control group consisted of sixteen patients, who were matched regarding age, gender and treatment duration, but who had undergone fixed orthodontic treatment without intrusion mechanics for molars. Tooth lengths were measured on pretreatment and posttreatment panoramic radiographs and mesiobuccal and distobuccal roots of left and right maxillary first molars were measured onscreen using a software program. Comparison of the differences in root resorption of the two groups showed a statistically significant difference only for the right mesial roots with a mean difference of only 0.5 mm. As a conclusion the root resorption of maxillary first molars after intrusion done using zygomatic skeletal anchorage is clinically not significant.
Keywords: Ortadonti